Personnel facilities in small workplaces with special reference to occupational health services. - Vaaranen, Anika; Kolivuori, Terttu; Rossi, Kitta; Tolonen, Matti; Hassi, Juhani (Scandinavian Journal of Work, Environment & Health, 1979)
The personnel facilities of small workplaces generally complied with the requirements. Yet, defects were detected in 20% of the 163 firms surveyed. Most of the faults were insignificant from the point of view of health. The failures were due to the fact that the facilities had not originally been planned for their present purpose. The need for the inspection of sanitary installations such as toilets and washrooms and facilities for storing and drying clothes was noted in dirty jobs and in places of work with toxicologic hazards. The management of small firms rarely needs medical advice on sanitary, catering and welfare amenities.
Keywords: nursing; occupational health nursing; occupational health service; personnel facility; small enterprise; small workplace